2014
DOI: 10.3390/ijms150711294
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Serum Chemerin Levels on Liver Functional Reserves and Platelet Counts in Patients with Hepatocellular Carcinoma

Abstract: Obesity-related metabolic abnormalities, including adipokine imbalance and chronic inflammation, are involved in liver carcinogenesis. Chemerin, a novel adipokine, plays a critical role in adipogenesis, energy metabolism, and inflammation. We evaluated the impact of serum chemerin levels on liver functional reserves in hepatocellular carcinoma (HCC) patients and on the recurrence and prognosis of HCC. This study included 44 patients with any stage of HCC who underwent curative treatment at Gifu Municipal Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 39 publications
2
36
2
Order By: Relevance
“…In individuals with liver cirrhosis, the adipose tissue atrophies, which is likely to additionally reduce the production of chemerin. Imai et al have demonstrated that levels of chemerin in patients with liver cirrhosis complicated by HCC were inversely correlated with Child-Pugh scores [18]. Moreover, the results of the current study have shown that serum chemerin levels were significantly correlated with platelet counts.…”
Section: Discussionsupporting
confidence: 69%
“…In individuals with liver cirrhosis, the adipose tissue atrophies, which is likely to additionally reduce the production of chemerin. Imai et al have demonstrated that levels of chemerin in patients with liver cirrhosis complicated by HCC were inversely correlated with Child-Pugh scores [18]. Moreover, the results of the current study have shown that serum chemerin levels were significantly correlated with platelet counts.…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, serum chemerin is inversely related to Child-Pugh score, serum alanine aminotransferase and total bilirubin. Chemerin in serum is not associated with survival [61]. …”
Section: Chemerin Expression and Serum Levels In Hepatocellular Carcimentioning
confidence: 99%
“…Gastric cancer is one type of cancer that has been well studied for its relationship with plasma levels of chemerin [16]. Other types of cancers that have been studied for their associations with chemerin include ovarian cancer, liver cancer, lung cancer, esophageal cancer, and colorectal cancer [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%